An Explicit Superconvergent Weak Galerkin Finite Element Method for the Heat Equation (Advances in Applied Mathematics and Mechanics, 2024)
An explicit two-order superconvergent weak Galerkin finite elementmethod is designed and analyzed for the heat equation on triangular and tetrahedral grids. For two-order superconvergent $P_k$ weak Galerkin finite elements, the auxiliary inter-element functions must be $P_{k+1}$ polynomials. In order to achieve the superconvergence, the usual $H^1$-stabilizer must be also eliminated. For time-explicit weakGalerkin method, a time-stabilizer is added, on which the time-derivative of the auxiliary variables can be defined. But for the two-order superconvergent weak Galerkinfinite elements, the time-stabilizer must be very weak, an $H^{−2}$-like inner-product instead of an $L^2$-like inner-product. We show the two-order superconvergence for bothsemi-discrete and fully-discrete schemes. Numerical examples are provided.